The Relationship between Exclusive Breastfeeding and Non-Exclusive Breastfeeding on the Incidence of Acute Respiratory Infection in Children aged 0-24 Months at YARSI Hospital Jakarta and its review according to an Islamic perspective - Shinta Aurellia Putri; Elsye Souvriyanti; Firman Arifandi (Junior Medical Journal, 2023)
Acute respiratory infections are the most important cause of morbidity in children. Based on the results of the 2018 Riskesdas, the highest category of the population experiencing ISPA was in the age range of 1-4 years (25.8%). The prevalence of ISPA according to the population age group 0 to 11 months was (9.4%). One of the factors that influence the incidence of ARI is the history of breastfeeding. Data obtained from the DKI Jakarta Province Health Profile shows that the coverage of exclusive breastfeeding in 2016 was 48.1% and decreased to 46.60% in 2017 with Central Jakarta City as the region with the lowest percentage of exclusive breastfeeding. The community needs to know the important role of exclusive breastfeeding both from a health perspective and from an Islamic point of view. This research is an analytic observational study using a cross-sectional design conducted on children aged 0-24 months at YARSI Hospital, Jakarta. After conducting a review based on the history of breastfeeding, the results of the Chi Square Test p 0.031 indicated that there was a relationship between exclusive breastfeeding and non-exclusive breastfeeding on the incidence of ARI in children aged 0-24 months at YARSI Hospital, Jakarta. Most mothers give exclusive breastfeeding which is in accordance with Islamic recommendations.